2012
DOI: 10.4049/jimmunol.1103715
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 Participates in the Development of Experimental Pneumococcal Meningitis by Augmentation of the Inflammatory Response via a TLR2-Dependent Mechanism

Abstract: In addition to a well-documented role in regulating T cell-mediated immune responses, B7-H3, a newly discovered member of the B7 superfamily, has been recently identified as a costimulator in the innate immunity-mediated inflammatory response. In this study, we further report that B7-H3 participates in the development of pneumococcal meningitis in a murine model. Exogenous administration of B7-H3 strongly amplified the inflammatory response, exacerbated blood–brain barrier disruption, and aggravated the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
1
36
1
Order By: Relevance
“…In the results of the present study, the reduction of NSE expression in the brain tissues of the mice treated with SP plus B7-H3 may reflect the following: i) NSE is primarily localized in the cytoplasm of neurons (10) and is not secreted; thus, an increase in its levels in the CSF or blood indicates structural damage of neuronal cells (8); ii) The number of existing functional neurons in the brain tissues that are available to be stained as NSE-positive by immunohistochemical analysis is markedly decreased due to apoptosis or necrosis caused by multiple factors exerting injurious effects, including exacerbated inflammation in (5), oxidative stress, lipid peroxidation, mitochondrial damage and BBB breakdown (1). Further reductions in NSE expression in brain tissues in response to combined SP and B7-H3 challenge indicate a greater degree of neuronal loss and structural neuronal damage, which is consistent with our previous study where it was identified that B7-H3 exacerbated the SP infection-induced proinflammatory response and BBB disruption (6). S100B belongs to the multi-genic family of Ca 2+ -binding proteins and is abundant in astrocytes, where it is found diffusely in the cytoplasm and is associated with membranes and cytoskeleton constituents (12).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In the results of the present study, the reduction of NSE expression in the brain tissues of the mice treated with SP plus B7-H3 may reflect the following: i) NSE is primarily localized in the cytoplasm of neurons (10) and is not secreted; thus, an increase in its levels in the CSF or blood indicates structural damage of neuronal cells (8); ii) The number of existing functional neurons in the brain tissues that are available to be stained as NSE-positive by immunohistochemical analysis is markedly decreased due to apoptosis or necrosis caused by multiple factors exerting injurious effects, including exacerbated inflammation in (5), oxidative stress, lipid peroxidation, mitochondrial damage and BBB breakdown (1). Further reductions in NSE expression in brain tissues in response to combined SP and B7-H3 challenge indicate a greater degree of neuronal loss and structural neuronal damage, which is consistent with our previous study where it was identified that B7-H3 exacerbated the SP infection-induced proinflammatory response and BBB disruption (6). S100B belongs to the multi-genic family of Ca 2+ -binding proteins and is abundant in astrocytes, where it is found diffusely in the cytoplasm and is associated with membranes and cytoskeleton constituents (12).…”
Section: Discussionsupporting
confidence: 81%
“…Our previous study (5) found an abnormally high expression level of soluble B7-H3 (sB7H3) protein in children with bacterial meningitis. In a murine model of SP-induced meningitis, we also demonstrated that B7-H3 further augmented the inflammatory response, exacerbated BBB disruption, and aggravated the pathological injury associated with the disease (6). In order to investigate the impact of B7-H3 on brain damage during SP-induced meningitis, the present study examined the effect of B7-H3 on neuronal necrosis and apoptosis and the protein expression of NSE and S100B in brain tissues in a murine model of SP-induced meningitis.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…A co-stimulatory role of B7-H3 on human T cells was initially reported in vitro (3). Murine studies showing B7-H3 worsens experimental autoimmune encephalomyelitis (EAE), arthritis, bacterial meningitis and chronic allograft rejection (1315) supported this claim. However, subsequent studies have mostly shown that B7-H3 acts as a T cell co-inhibitor.…”
Section: Introductionmentioning
confidence: 97%